2003
DOI: 10.1063/1.1596583
|View full text |Cite
|
Sign up to set email alerts
|

Weak ferromagnetism and an intermediate incommensurate antiferromagnetic phase in LiNiPO4

Abstract: The temperature dependence of the magnetization of single-crystal LiNiPO4 is measured for magnetic-field orientations along the a, b, and c crystallographic axes. It is found that the value of the magnetization depends on the magnetic prehistory of the sample. The magnetic behavior of the antiferromagnetic sample is explained by the presence of weak ferromagnetism in LiNiPO4. At a temperature of 5 K the value of the spontaneous magnetic moment along the c axis is around 0.005 G. When the sample is heated to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
2
22
1
1
Order By: Relevance
“…Recent neutron diffraction measurements of single crystal LiCoPO 4 reported finite intensity at the (010) reflection, interpreted in terms of a ground state with a spin direction that is slightly rotated from the b-axis [12]. Weak ferromagnetism has been reported for LiMnPO 4 [18] and LiNiPO 4 [19] at a temperature below T N .…”
Section: (B) For Definition Of Exchange Couplings)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent neutron diffraction measurements of single crystal LiCoPO 4 reported finite intensity at the (010) reflection, interpreted in terms of a ground state with a spin direction that is slightly rotated from the b-axis [12]. Weak ferromagnetism has been reported for LiMnPO 4 [18] and LiNiPO 4 [19] at a temperature below T N .…”
Section: (B) For Definition Of Exchange Couplings)mentioning
confidence: 99%
“…Nearest-neighbor (NN) spins in the b-c plane are anti-parallel and the stacking along the a-axis is such that ferromagnetic * electronic mail: jiy@ameslab.gov † electronic mail: vaknin@ameslab.gov sheets perpendicular to the b-axis are formed; nearest neighbor sheets are anti-parallel giving rise to (010) fundamental magnetic reflection that, depending on the direction of the magnetic moment, can be intense or extinct. Earlier neutron diffraction studies of polycrystalline samples showed that the magnetic space group of LiFePO 4 and LiCoPO 4 is Pnma' with the spins oriented along b crystallographic direction (i.e., the (010) reflection is absent), and Pnm'a magnetic space group for LiNiPO 4 and LiMnPO 4 with the spins aligned parallel to the c-axis (i.e., strong intensity at the (010) reflection) [11,12,15,16,17,18]. Recent neutron diffraction measurements of single crystal LiCoPO 4 reported finite intensity at the (010) reflection, interpreted in terms of a ground state with a spin direction that is slightly rotated from the b-axis [12].…”
Section: (B) For Definition Of Exchange Couplings)mentioning
confidence: 99%
“…On cooling LiNiPO 4 orders incommensurately at T N = 21.8 K, then orders commensurately at T IC−C = 20.7 K. 2,37 Neutron diffraction has characterized both the long-range ordered phases and found diffuse scattering well above T N . The trend in the magnetic order parameter approaching the breakup of collinear order was found to follow the dependence expected for a 2D Ising model; 38 an anomalous correlation between the spin wave spectrum and the incommensurate magnetic order 39 and coexisting short-and long-range incommensurate magnetic order were reported for the intermediate phase.…”
Section: A Linipomentioning
confidence: 99%
“…16 Here, it was found that LiNiPO 4 undergoes a first-order transition from the antiferromagnetic ground state to a long-range IC order at a Néel temperature, T N = 20.8 K ͑T N ϵ T C-IC ͒. As the temperature is increased, a second-order phase transition from the longrange incommensurate magnetic order to the paramagnetic state occurs at T IC = 21.7 K. 16,17 The incommensurate spin correlations gradually weaken and the spins are essentially PHYSICAL REVIEW B 79, 174435 ͑2009͒…”
Section: Introductionmentioning
confidence: 99%